Comparison of Lead Zirconate Titanate Properties between the Pressing Process and the Gel Casting Process by using Ethylene Glycol Diglycidyl Ether (EGDGE) Epoxy Resin as a Gelling Agent - Thongchai, Tanikan (Naresuan University Journal: Science and Technology (NUJST), 2020)
Gel casting has been widely developed during the past ten years due to its applicability in the complex shape fabrication of small ceramic products such as transducers and sensors, and this process provides a low-cost manufacturing route. The purpose of this research is to focus on the PZT properties resulting from the pressing and gel casting processes. In the pressing process, a soft PZT 5H powder was pressed using an Instron testing machine under 90 MPa. In the gel casting process, the ethylene glycol diglycidyl ether (EGDGE) epoxy monomer and a solution of an ammonium salt of an acrylic polymer in water (NH 4 PAA) were utilised as a gelling agent and dispersant, respectively. The results showed that the viscosity of the PZT was minimised by adding 1.2 wt% of the dispersant. The highest green strength of approximately 35 MPa was found from the pressed sample. In the gel casting process, at 40 wt% EGDGE resin content and 46 vol% solids loading provided the highest green strength of approximately 30 MPa. The PZT samples from both processes were sintered at 1,200 °C. The sample from the pressing process provided the highest values of d 33 , k p and ε r of approximately 590 pC/N, 0.62, and 2,875, respectively; while the PZT samples fabricated from a gel casting slurry incorporating a 40 wt% EGDGE resin and 46 vol% solids loading provided d 33 , k p and ε r values of approximately 575 pC/N, 0.6, and 2800, respectively. The results indicated that the desired properties of the pressed PZT sintered samples were slightly higher than those of the properties of the PZT gel cast samples. Keywords: PZT, Piezoelectric, Dielectric, EGDGE Epoxy Resin, Gel Casting